The performance measurement and productivity change of agro and food industry in the stock exchange of Thailand - Rapee Pongpanich (2018)
© 2018, Agricultural Economics. All rights reserved. At present, the agro and food industry has a high influence to farmers in Thailand. Most of the raw materials of agriculture are sent to its manufactoring. This industry has an important role to raise the growth of the Thai economy. The main objective of the paper is to study the production trends and ability operations of the agro and food industry by using economic tools analyse two sub-industry sectors. The paper reviewed literatures on the performance measurement and productivity change of the business sector to obtain the relative variables and optimal methodology. The paper designed to use the panel data of the agro and food industry during the period 2011–2014. The Slacks-based Measure context-dependent Data Envelopment Analysis (SBM context-dependent DEA) was used to analyse the efficiency and ability in the Decision Making Units (DMUs) by employing the attractiveness and progress score. Moreover, the Malmquist index was used to demonstrate the change of the total productivity of this industry. Therefore, the empirical results of the paper can help the companies inside and outside the stock exchange of the agro and food industry to realize the performance level and benchmark leading to the improvement of their operation. Moreover, they help the government to develop its policy and to understand the character of the sub-industry sectors and the productivity trend in this industry.